2001
DOI: 10.2307/2657129
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships and evolution of Crassulaceae inferred from matK sequence data

Abstract: Chloroplast gene matK sequence data were used to estimate the phylogeny of 112 species of Crassulaceae sampled from 33 genera and all six recognized subfamilies. Our analyses suggest that five of six subfamilies recognized in the most recent comprehensive classification of the family are not monophyletic. Instead, we recovered a basal split in Crassulaceae between the southern African CRASSULA: clade (Crassuloideae) and the rest of the family (Sedoideae). These results are compatible with recent studies of cpD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
145
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 39 publications
(96 reference statements)
9
145
1
2
Order By: Relevance
“…This pattern has been found in many previous studies of Sedum phylogeny conducted using RAPD analysis (Kwon and Jeong, 1999), matK sequence data (Mort et al, 2001), and chloroplast data (Van Ham and 'T Hart, 1998). In the matK sequence analysis by Mort et al (2001), the phylogeny revealed the polyphylic nature of Sedum species, with S. sexangulare, S. oryzifolium, and S. sarmentosum classified into the Acre clade in the Sedoideae subfamily, while S. rupestre was included in the Sempervivum clade in the Sedoideae subfamily. The polyphyletic position of S. rupestre, as observed in this study, may be explained as follows-in morphological, phenological, and biogeographical contexts, S. rupestre was distinguished with other Sedum species classified in the Acre clade.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…This pattern has been found in many previous studies of Sedum phylogeny conducted using RAPD analysis (Kwon and Jeong, 1999), matK sequence data (Mort et al, 2001), and chloroplast data (Van Ham and 'T Hart, 1998). In the matK sequence analysis by Mort et al (2001), the phylogeny revealed the polyphylic nature of Sedum species, with S. sexangulare, S. oryzifolium, and S. sarmentosum classified into the Acre clade in the Sedoideae subfamily, while S. rupestre was included in the Sempervivum clade in the Sedoideae subfamily. The polyphyletic position of S. rupestre, as observed in this study, may be explained as follows-in morphological, phenological, and biogeographical contexts, S. rupestre was distinguished with other Sedum species classified in the Acre clade.…”
supporting
confidence: 84%
“…The RAPD-based grouping of 31 S. sarmentosum ecotypes distributed in Korea was strongly related to morphological characteristics (Kim et al, 2008). This pattern has been found in many previous studies of Sedum phylogeny conducted using RAPD analysis (Kwon and Jeong, 1999), matK sequence data (Mort et al, 2001), and chloroplast data (Van Ham and 'T Hart, 1998). In the matK sequence analysis by Mort et al (2001), the phylogeny revealed the polyphylic nature of Sedum species, with S. sexangulare, S. oryzifolium, and S. sarmentosum classified into the Acre clade in the Sedoideae subfamily, while S. rupestre was included in the Sempervivum clade in the Sedoideae subfamily.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…The series Rupestria was raised to the genus level (Petrosedum Grulich) in the 1984 and recent molecular studies (Mort et al, 2001) confirm the soundness of splitting the polyphyletic genus Sedum into many small new genera, series Rupestria included. However, this split is not yet recognised formally (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Members of this family are leaf-succulent, usually herbaceous, and often have fi veparted, radially symmetrical fl owers with two whorls of fi ve stamens each. Reported secondary metabolites from Crassulaceae species are fl avonoids, steroids, alkaloids and triterpenoids (Mort et al, 2001).…”
Section: Introductionmentioning
confidence: 99%